(untitled) - Kuhn, Thomas S. (Cambridge, 1985)
This is a book for any reader interested in the evolution of ideas and, in particular, in the curious interplay of hypothesis and experiment which is the essence of modern science.
Keywords: Cosmology,Vũ trụ học